Building the Foundation: Whole Numbers in the Primary Grades: The 23rd ICMI Study - Bartolini Bussi, Maria G.; Sun, Xu Hua (New ICMI Study Series, 2018)
mathematics teaching and learning in the primary school; whole number arithmetic; 23rd ICMI Study; international perspectives on primary math education; social-cultural diversity of early mathematics teaching; institutional constraints of early mathematics; whole number thinking, learning and development